2010
DOI: 10.1016/j.neuroscience.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Age exaggerates proinflammatory cytokine signaling and truncates signal transducers and activators of transcription 3 signaling following ischemic stroke in the rat

Abstract: Neuroinflammation is associated with glial activation following a variety of brain injuries, including stroke. While activation of perilesional astrocytes and microglia following ischemic brain injury is well documented, the influence of age on these cellular responses after stroke is unclear. This study investigated the influence of advanced age on neuronal degeneration, neuroinflammation, and glial activation in female Sprague-Dawley rats after reversible embolic occlusion of the middle cerebral artery (MCAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
6
61
0
Order By: Relevance
“…It is thus still unclear whether aging exerts its effects via stimulation of excessive or dysregulated inflammatory responses. This hypothesis is supported by previous studies showing that aged animals have altered immune responses resulting from ischemic insult (Kharlamov et al, 2000;PopaWagner et al, 2007;Dinapoli et al, 2010;Sieber et al, 2011), intracerebral hemorrhage (Lee et al, 2009) or mechanical injury (Kyrkanides et al, 2001). However, mechanisms through which aging interacts with systemic inflammation to influence cerebrovascular pathologies remain unclear.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is thus still unclear whether aging exerts its effects via stimulation of excessive or dysregulated inflammatory responses. This hypothesis is supported by previous studies showing that aged animals have altered immune responses resulting from ischemic insult (Kharlamov et al, 2000;PopaWagner et al, 2007;Dinapoli et al, 2010;Sieber et al, 2011), intracerebral hemorrhage (Lee et al, 2009) or mechanical injury (Kyrkanides et al, 2001). However, mechanisms through which aging interacts with systemic inflammation to influence cerebrovascular pathologies remain unclear.…”
Section: Introductionsupporting
confidence: 63%
“…Cerebral inflammation is elevated with aging (Sieber et al, 2011), and aged animals have been reported to show an increase in proinflammatory mediators after ischemia (Dinapoli et al, 2010), intracerebral hemorrhage (Lee et al, 2009), or mechanical injury (Kyrkanides et al, 2001). In the current study, the brain peri-infarct levels of MCP-1, KC, IL-1a, and RANTES were elevated after brain ischemia in aged mice compared with their young counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…10 Hippocampal protein samples were dissolved in 0.5 ml hot (85°-95°C) 1% sodium dodecyl sulfate, sonicated, and assayed with a bicinchoninic acid protein assay kit (Thermo Fisher Scientific). Thirty micrograms of protein per well was run with 2× Laemmli buffer on precast Bolt Bis-Tris Plus 10% 12-well gels (Life Technologies) using a Bolt Mini tank system (Life Technologies).…”
Section: Western Blotmentioning
confidence: 99%
“…SOCS3 expression is induced or upregulated in various brain regions including hippocampus and lateral ventricles in response to CNTF administration [197], ischemic stroke [198,199] and seizure, which also showed transient downregulation of hippocampal SOCS2 expression but no upregulation of SOCS1 [200]. Conversely, after transient forebrain ischemia, SOCS2 expression was upregulated in the hippocampus, not only in astrocytes but also a subset of nestin positive NPCs [201].…”
Section: Socs Proteins and Cns Injurymentioning
confidence: 99%